2018
DOI: 10.2174/1874350101811010065
|View full text |Cite
|
Sign up to set email alerts
|

Animal, Human and Robot Attribution: Ontologization of Roma, Romanian and Chinese Groups in an Italian Sample

Abstract: Background: The socio-psychological ontologization approach focuses on the attribution of a different “ontology” to outgroup members, that is the attribution of animal (or natural) attributes to the outgroup, and human (or cultural) attributes to the ingroups. Objectives: This study aims to enrich the ontologization approach in two ways: (1) A theoretical development of the ontologization approach is proposed, by incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Traditionally, studies on the ontologization processes had focused only on the first two dimensions, that is, animal and human essence. Pivetti et al (2018) have investigated the attribution of three essences, that is, the animal, human and automata one, to 1 the Roma, Romanian and Chinese target, but have not provided any factorial validation of the proposed model. In this study, using CFA, we found that the model including human, animal and automata associates was statistically robust for each of the three target groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, studies on the ontologization processes had focused only on the first two dimensions, that is, animal and human essence. Pivetti et al (2018) have investigated the attribution of three essences, that is, the animal, human and automata one, to 1 the Roma, Romanian and Chinese target, but have not provided any factorial validation of the proposed model. In this study, using CFA, we found that the model including human, animal and automata associates was statistically robust for each of the three target groups.…”
Section: Discussionmentioning
confidence: 99%
“…As per the definition, the ontologization approach consists in the attribution of animal characteristics, besides Pivetti et al (2018), to our knowledge, no studies have been conducted to investigate the attribution of a different ontology to outgroup members in terms of automata. Pivetti et al (2018) has proposed a theoretical development of the ontologization approach, which also includes the attribution to outgroup members of a "robot" essence, in addition to the animal essence. This study confirmed the animalization of the Roma people in Italy resulting from ingroup members attributing animallike associates to them and denying human-like associates.…”
Section: Overview and Aims Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Participants also attributed two animal (dirty and free) and two human (selfish and rational) traits to the depicted (step)mother on a 5-point Likert scale (1 = not at all; 5 = very well). Animal and human traits were the same ad-hoc items of previous studies on ontologization of "non-traditional" parents and other minority groups (see in Di Battista et al 2020b;Berti et al 2013;Pivetti et al 2018) (animal: M = 2.42, SD = 0.81; r = 0.31, p < 0.001; Skewness = 0.34, Kurtosis = 0.83; human: M = 2.82, SD = 0.82; r = 0.26, p < 0.001; Skewness = −0.02, Kurtosis = 0.37).…”
Section: Methodsmentioning
confidence: 99%
“…Literature on the Chinese living in Italy is limited, with some exceptions (see e.g., Cologna 2005;Pedone 2011;Barbieri and Zani 2015;Ottati and Cologna 2015) to the national research audience, and published mainly in Italian (Ceccagno 1999;Cologna 2002Cologna , 2009Cologna and Breveglieri 2003;Pedone 2004Pedone , 2008. Moreover, most of the literature regarding the migrants living in Italy is focused on discrimination (see e.g., Cariota Ferrara and La Barbera 2008;Pivetti et al 2018) and the attitudes (see e.g., Castellini et al 2011) of the host society toward them. Few studies, on the other hand, focus on the representation of Chinese immigrants of their host society and how it affects their experience.…”
Section: Theoretical Frameworkmentioning
confidence: 99%